Upaya Peningkatan Produktifitas UMKM Batik di Kabupaten Kuantan Singingi - Adelia Ismaya; Febri Yuliani (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
MSMEs have the potential to support economic growth in driving the national economy. In an effort to increase the productivity of batik MSMEs, the government created Kuantan Singingi Regent Regulation Policy No. 36 of 2021. This policy states that batik is made into ASN and honorary uniforms. Every ASN and honorary employee is required to wear Kuansing Batik every Thursday. With this regulation, it is hoped that demand for batik production will increase so that it can increase the economic value for batik MSMEs in Kuantan Singingi. The research method used in this research is a qualitative method. Data collection techniques use interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions and verification. The research results show that with the Kuantan Singingi Regent's regulatory policy No. 36 of 2021 concerning efforts to increase the productivity of Batik MSMEs in Kuantan Singingi Regency, there has been an increase in demand for Kuantan Singingi batik. Apart from the Kuantan Singingi Regent's regulation No. 36 of 2021, the production of Kuantan Singingi batik MSMEs is also assisted by the Kuantan Singingi Regency Small and Medium Enterprises Cooperatives, Trade and Industry Service as an instructor and provides training to Kuntan Singingi batik craftsmen. Apart from that, the Department of Small and Medium Enterprises Cooperatives, Trade and Industry of Kuantan Singingi Regency introduces Kuantan Singingi batik to the wider community by participating in various expos both nationally and internationally. The factors inhibiting the implementation of the Kuantan Singingi Regent's regulatory policy No. 36 of 2021 as an effort to increase the productivity of Batik MSMEs in Kuantan Singingi Regency are the lack of capital and high selling prices to consumers.